The Existence of Totokng Dance as the Cultural Identity of the Dayak Salako Tribe - Slamet, Deni; Narawati, Tati; Budiman, Agus (Universitas Negeri Medan, 2025)
This study aims to examine the existence of the Totokng dance in the Nurutni’ Ceremony as a representation of the cultural identity of the Dayak Salako community in West Kalimantan. The dance functions not only as a performative expression but also as a medium of spiritual communication that connects humans, ancestors, nature, and God (Jubato). This research adopts a qualitative descriptive approach, using participatory observation, semi-structured interviews, and field documentation in Pelanjau Hamlet, the central site of the ceremony. The findings show that the Totokng dance is a sacred ritual passed down vertically through the ancestral lineage of the Panglima Kayau. The structure of the performance consists of preparation, main performance, and post-ritual stages, with strong symbolism reflected in the movements, music, costumes, and offerings. The dance embodies cosmological and spiritual values, turning the dancer’s body into a living archive of collective memory. The shift in the function of the dance from a symbol of power to a ritual of gratitude for the harvest illustrates the adaptive capacity of local culture in facing social change. The process of intergenerational transmission through direct ritual experience strengthens the preservation of its meaning. In conclusion, the Totokng dance not only maintains ancestral traditions but also acts as a cultural instrument that reinforces the identity and resistance of the Dayak Salako community in the face of global cultural homogenization.